2017
DOI: 10.21608/tsnj.2017.71157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intervention Guidelines on Nurses' Performance Regarding Prevention and Management of Intravenous Extravasation Chemotherapy for Children

Abstract: Background: Extravasation of chemotherapy is accidental leakage of chemotherapy drugs into the subcutaneous tissue tissues surrounding the administration site. Aim of the study was to evaluate the effect of intervention guidelines for prevention and management of intravenous extravasation chemotherapy on nurses' performance. Quasi-experimental research design was used. It was carried out at Pediatric Hematology and Oncology Unit of Tanta University Hospital. A convenient sample of 20 nurses working in Pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…systematic implementation of intervention that alleviating the extravasation injuries and improving the patients' outcome, in addition, the finding of the present study is consistent with Boyar & Galiczewski (2021) they concluded that, the overall rate of adherence to the peripheral intravenous catheter securement guideline was between 80% and 98%. between studied nurses' group, which associated with a marked decrease in prevalence of extravasation.Furthermore, the finding was in line with El-Hamed et al (2017) they found that significant improvement in nursing staff knowledge and performance after implantation of prevention and management of chemotherapy extravasation guideline. About hypothesis three: the incidence rate of infiltration and extravasation would be reduced posttest than pretest.…”
Section: Discussionsupporting
confidence: 82%
“…systematic implementation of intervention that alleviating the extravasation injuries and improving the patients' outcome, in addition, the finding of the present study is consistent with Boyar & Galiczewski (2021) they concluded that, the overall rate of adherence to the peripheral intravenous catheter securement guideline was between 80% and 98%. between studied nurses' group, which associated with a marked decrease in prevalence of extravasation.Furthermore, the finding was in line with El-Hamed et al (2017) they found that significant improvement in nursing staff knowledge and performance after implantation of prevention and management of chemotherapy extravasation guideline. About hypothesis three: the incidence rate of infiltration and extravasation would be reduced posttest than pretest.…”
Section: Discussionsupporting
confidence: 82%
“…This tool was developed by the researcher after reviewing recent related literature (Al-Naeli, & Hassan, 2021 ;Beaver, 2018 ;El-Hamed, Mahmoud, Bahgat, Marie, & El Sayed, 2017) to assess nurses' practice level regarding prevention and management of chemotherapy extravasation. It was checked by researcher as done and not done pre-posttest.…”
Section: Scoring Systemmentioning
confidence: 99%